Biogenesis-Inspired Synthesis of Penicillitone - Bauer, Maximilian; Heretsch, Philipp (Synthesis, 2023)
The biogenesis-inspired synthesis of the structurally unique 15(14→11)abeo-steroid penicillitone starting from commercially available ergosterol is reported. Key to the strategy is an intramolecular vinylogous aldol reaction of a 14,15-secoergostane obtained from the previously reported 14,15-secosteroid platform. Since a similar intermediate has been employed to access the strophasterol class of natural products, this work points at a possible biosynthetic connection between penicillitone and the strophasterols.
Keywords: abeo-steroids; biogenesis-inspired synthesis; intramolecular vinylogous aldol reaction; penicillitone; strophasterol